Short arms of human acrocentric chromosomes and the completion of the human genome sequence - Antonarakis, Stylianos E.

(untitled) (Genome Research, 2022)
The complete, ungapped sequence of the short arms of human acrocentric chromosomes (SAACs) is still unknown almost 20 years after the near completion of the Human Genome Project. Yet these short arms of Chromosomes 13, 14, 15, 21, and 22 contain the ribosomal DNA (rDNA) genes, which are of paramount importance for human biology. The sequences of SAACs show an extensive variation in the copy number of the various repetitive elements, the full extent of which is currently unknown. In addition, the full spectrum of repeated sequences, their organization, and the low copy number functional elements are also unknown. The Telomere-to-Telomere (T2T) Project using mainly long-read sequence technology has recently completed the assembly of the genome from a hydatidiform mole, CHM13, and has thus established a baseline reference for further studies on the organization, variation, functional annotation, and impact in human disorders of all the previously unknown genomic segments, including the SAACs. The publication of the initial results of the T2T Project will update and improve the reference genome for a better understanding of the evolution and function of the human genome.